Convergence Problems in the Eurozone - Wierzejski, Tomasz; Siemionek, Małgorzata (Olsztyn Economic Journal, 2012)
This paper analyses the issue of convergence in the Eurozone. The overarching objective was to evaluate the monetary and fiscal convergence of the countries in the Eurozone during the recent period. A further goal was to establish recommendations boosting the economic efficiency of the analysed currency integration of the Eurozone. The paper pinpoints crucial theoretical underpinnings and the current analysis of the Eurozone. Empirical data pertinent to macroeconomic indicators, which were collated and statistically analysed, were also used to delineate crucial issues of convergence in the Eurozone.